A Measure of Entrepreneurial Behavior of University Students: A Theory of Planned Behavior Approach - Setiaji, Khasan (Dinamika Pendidikan, 2018)
Higher education institutions should be able to change the mindset of students who are not only as job seekers, but also job creators especially when educated unemployment in Indonesia increases every year. Entrepreneurship is one solution in tackling unemployment and poverty which will encourage national economic growth. This study examines the effect of self-efficacy and contextual environment on entrepreneurial behavior with entrepreneurial intention as an intervening variable using Theory of Planned Behavior. The subjects of this study were Semarang State University students who owned a business and joined the UNNES Student Entrepreneurship Center (UNSEC) and Himpunan Pengusaha Muda Indonesia Perguruan Tinggi (HIPMI PT) Semarang State University totaling 310 students. The results showed a direct relationship between self-efficacy and contextual environment towards entrepreneurial behavior and indirect relationships through entrepreneurial intentions. It was proved by the moderating role of entrepreneurial intention in facilitating the relationship of self-efficacy and contextual environment to student entrepreneurial behavior in accordance with the Theory of Planned Behavior. Future studies can use elements of social and demographic psychology that are more complete and involve a wider population.